Hibridisasi Buatan Kacang Tanah dan Fenotipe Karakter Tipe Pertumbuhan, Ukuran Polong, dan Jumlah Biji per Polong Tanaman F1 Hasil Hibridisasi - Setyo Dwi Utomo; Kuswanta Futas Hidayat; Akari Edy; Nyimas Sa'diyah; Rizki Indriyani; Emma Halimaturosidah; Herlin Yustina (Universitas Lampung, 2021)
The development of superior peanut cultivars can be conducted through the steps of enhancement of genetic variation, inbreeding, selection, and yield trials. Genetic variation can be enhanced through sexual hybridization (crossing). The objectives of this study were 1) to determine the rate of success of artificial hybridization between runner/semi-runner and Spanish/upright type of peanut; 2) to know the phenotypic characters of the growth habit, pod size, and number of seeds per pod in peanuts. The F1 phenotype is related to the estimation of gene action. This study consisted of two experiments, namely hybridization and evaluation of the type of growth of the F1 family. The experiment was conducted in the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung. The genotypes of parents included national cultivars Bima, Bison, Gajah, Jerapah, Talam, and Kelinci; and introduced runner/semi-runner genotypes K / SR-3 (runner) and NC 7 (semi-runner). The results showed that NC 7 x Bison showed the highest ratio of the number of gynophores (NG) / number of flowers crossed (NFC) (31%); NC 7 x Kelinci showed the highest number of pods (NP) / NG ratio (78%); and Bima x NC 7 showed the highest NP / NFC (13%). The percentage of F1 plants showing semi-runner growth habit was 85%, producing pods with two seeds was 100%, and producing large pods was 89%. Keywords: Growth habit, pod size, the rate of artificial hybridization, seed number